Kajian Desulfurisasi pada Pembakaran Biobriket dengan Adsorben Berbasis Kalsium - - Kamarullah; - Khairil; - Mahidin (Jurnal Teknik Mesin Unsyiah, 2013)
Combustion of biobriquette produced from coal and palm shell generate considerable energy. However beside generating biobriquette energy it also produces emissions gas. Emissions gas resulting from combustion include SOx, NOx, CO and CO2. Calcium is an adsorbent often used to adsorb released SO2 gas in the combustion process. The purpose of this study is to seethe effect of combustion temperature and type of adsorbent used in biobriquette to evaluate the efficiency of absorption of SO2 and the kinetics of the reaction of SO2 gasabsorption as a function of combustion biobriquette ratio Ca/S (mol / mol) on coal and palm shell ratio of 90:10 (w/w). In this study, the ratio of Ca/Swas Specified at1:1, 1.25:1, 1.5:1, 1.75: 1 and 2:1. Combustion temperatures used were 300, 350, 400, 450 and 500°C. The result of this study showed the decrease levels of SO2 for scallop shell and green mussels  was highest at the ratio Ca/S2: 1. The highest absorption of efficiency adsorbent for scallop shells are produced at the ratio of Ca/2:1 at temperatures 400°C, equals to 90.59%. Meanwhile for the green mussels, the highest efficiency was resulted ratio of Ca/S 1.5:1 at temperatures 400°C which was equals to 84.74%. Reaction rate constants of absorption in the biggest adsorbent of scallop shells produced at ratio Ca/S 1:1 equals to  0.265, while the biggest reaction rate constants of adsorbent green mussels produced at being Ca/S 1.5:1equals to  0,198.